2017
DOI: 10.2489/jswc.72.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Drainage water management effects over five years on water tables, drainage, and yields in southeast Iowa

Abstract: Subsurface drainage improves row crop production but also short circuits nitrate-nitrogen (NO 3-N) pathways in the soil with significant losses to surface waters. The objective of this study was to evaluate the effect of shallow, controlled, conventional, and undrained drainage treatments on depth to water table, drainage volume and NO 3-N loads, soil water content and storage in the soil profile, and crop yields. This research was conducted at the Iowa State University Southeast Research Farm near Crawfordsvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 21 publications
(27 reference statements)
5
28
0
Order By: Relevance
“…Additionally, corn hybrids can be selected that have greater resilience to early season suboptimal temperatures (Gupta 1985). At this site, drainage volumes and NO 3 loss were reduced by 60% and 61% for the controlled drainage treatment and 58% and 49% for the shallow drainage treatment, respectively, when compared to conventional drainage for the five-year period from 2011 to 2015 (Schott et al 2017). Thus, at this site, drainage water management substantially reduced NO 3 loss without delaying planting or reducing yields.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…Additionally, corn hybrids can be selected that have greater resilience to early season suboptimal temperatures (Gupta 1985). At this site, drainage volumes and NO 3 loss were reduced by 60% and 61% for the controlled drainage treatment and 58% and 49% for the shallow drainage treatment, respectively, when compared to conventional drainage for the five-year period from 2011 to 2015 (Schott et al 2017). Thus, at this site, drainage water management substantially reduced NO 3 loss without delaying planting or reducing yields.…”
Section: Methodsmentioning
confidence: 87%
“…All drainage treatments were planted on the same day due to plot layout, and the field manager decided when field conditions were suitable for planting. Yield methodology was outlined in Helmers et al (2012) and reported in Schott et al (2017). When necessary, the boards in the controlled drainage treatments were removed in mid-to late April for approximately two weeks prior to planting to allow free drainage and replaced in late May to early June after planting.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations